PENGARUH PEMBERIAN N-ACETYLCYSTEINE (NAC) TERHADAP KADAR MALONDIALDEHYDE (MDA) PADA PENDERITA DIABETES MELITUS TIPE 2 - Putri, Athifa Alya; Yerizel, Eti; Miro, Saptino (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Several classifications of diabetes mellitus include type 1 diabetes, type 2 diabetes, gestational diabetes, and other types of diabetes. Type 2 diabetes is caused by insulin resistance. Hyperglycemia in type 2 diabetes patients causes cell and tissue damage through oxidative stress processes. One of the main biomarkers of oxidative stress levels that can be analyzed is malondialdehyde levels. To reduce ROS levels, a definitive therapy is needed, which is the administration of exogenous antioxidants, one of which is N-Acetylcysteine (NAC) therapy. NAC works by forming glutathione antioxidants, which aim to fulfill the body's natural antioxidant deficit in overcoming hyperglycemia conditions. This study was a true experimental research study with a pre-posttest research design. The sample used was 20 patient blood serum samples, which were measured for MDA levels before NAC administration. Then, NAC therapy was administered at a dose of 3X400 mg per day for 5 weeks, and MDA levels were measured after the therapy using the Thiobarbituric Acid Reactive Substance (TBARS) method. The results of the study showed that the mean MDA level after NAC administration and the mean MDA level before NAC administration were 2.76 ± 0.251 nmol/ml and 3.28 ± 0.427 nmol/ml, respectively. There was a significant decrease in MDA levels in the blood serum of type 2 diabetes patients with a value of p = 0.000 (p <0.5). Thus, it can be concluded that the use of NAC has an effect on reducing MDA levels in type 2 diabetes mellitus patients